Inactivation of Minar2 in mice hyperactivates mTOR signaling and results in obesity - Saran Lotfollahzadeh; Chaoshuang Xia; Razie Amraei; Ning Hua; Konstantin V. Kandror; Stephen R. Farmer; Wenyi Wei; Catherine E. Costello; Vipul Chitalia; Nader Rahimi (Elsevier, 2023)
Objective: Obesity is a complex disorder and is linked to chronic diseases such as type 2 diabetes. Major intrinsically disordered NOTCH2-associated receptor2 (MINAR2) is an understudied protein with an unknown role in obesity and metabolism. The purpose of this study was to determine the impact of Minar2 on adipose tissues and obesity. Method: We generated Minar2 knockout (KO) mice and used various molecular, proteomic, biochemical, histopathology, and cell culture studies to determine the pathophysiological role of Minar2 in adipocytes. Results: We demonstrated that the inactivation of Minar2 results in increased body fat with hypertrophic adipocytes. Minar2 KO mice on a high-fat diet develop obesity and impaired glucose tolerance and metabolism. Mechanistically, Minar2 interacts with Raptor, a specific and essential component of mammalian TOR complex 1 (mTORC1) and inhibits mTOR activation. mTOR is hyperactivated in the adipocytes deficient for Minar2 and over-expression of Minar2 in HEK-293 cells inhibited mTOR activation and phosphorylation of mTORC1 substrates, including S6 kinase, and 4E-BP1. Conclusion: Our findings identified Minar2 as a novel physiological negative regulator of mTORC1 with a key role in obesity and metabolic disorders. Impaired expression or activation of MINAR2 could lead to obesity and obesity-associated diseases.